Interplay of C Alloying, Temperature, and Microstructure in Governing Mechanical Behavior and Deformation Mechanisms of High-Manganese Steels - Chenghao Zhang; Jinfu Zhao; Tengxiang Zhao; Ling Kong; Chunlei Zheng; Haokun Yang; Yuhui Wang (Metals, 2025)
This study investigates the mechanical behavior and deformation mechanisms of Fe-30Mn-0.05C (30Mn0.05C) and Fe-34Mn-0.7C (34Mn0.7C) steels at room temperature (RT) and liquid nitrogen temperature (LNT). The 30Mn0.05C sample exhibited a significant enhancement in both strength and ductility at LNT, achieving a total elongation of 85%. In contrast, the 34Mn0.7C sample demonstrated superior ductility (90%) at RT, with a marginal reduction in plasticity but a remarkable increase in strength (>1100 MPa) at LNT. Compared to the 30Mn0.05C, the 34Mn0.7C, characterized by higher carbon content, displayed more pronounced dynamic strain aging (DSA) effects. Additionally, a greater density of deformation twins was activated at LNT, revealing a strong correlation between deformation twinning and DSA effects. This interplay accounts for the simultaneous strength improvement and ductility reduction observed in the 34Mn0.7C at LNT. Furthermore, the 34Mn0.7C sample exhibited a significantly refined grain structure after rolling, contributing to a substantial strength increase (approaching 1500 MPa) at the expense of ductility. This trade-off can be attributed to the pre-introduction of a higher density of dislocations and deformation twins during rolling, which facilitated strengthening but limited further plastic deformation.